Leveraging innovation for electricity utilities - Tayal, Dev (Elsevier Inc., 2017)
© 2017 Elsevier Inc. Innovations in energy products and services, facilitated through effective partnerships with research centers, may provide benefits to utilities across the value chain. Policy implications could be significant in shifting from traditional regulatory models to flexible frameworks that encourage innovation. A collaborative mindset will be needed to ensure utilities recognize the role they must also play in guiding regulatory reform.